Семантика противительности в синхронии и диахронии - Милованова, Мария (Studia Rossica Posnaniensia, 2015)
The author of this article presents the semantics of adversativity as subjective contraposition (vs. spatial, logical and grammatical contraposition). The article discusses the history of the transformation of spatial meaning into adversative meaning. Basic examples include words that belong to the same etymological family, such as против, напротив, противный, прочь, прямо и просто (which are equivalents of the Polish words: przeciw, naprzeciw, przeciwko, przeciwnie, przecie(ż), oprócz, etc.).